Modal Literasi Menuju Kemandirian: Sebuah Program Pemberdayaan bagi Komunitas Perwakos Kota Surabaya - Robertus Adi Nugroho; Thyophoida Panjaitan; Dita Natasya Handriyani Soeprapto; Novi Puspita Kihie Halimaking (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community engagement program aims to empower the Perwakos Community (Persatuan Waria Kota Surabaya), a transgender community in Surabaya, by strengthening their financial literacy and facilitating the development of a structured community business plan. Initial assessments revealed two critical challenges faced by the community: limited financial management skills at both individual and collective levels, and the absence of a formal business plan to guide potential economic initiatives. To address these issues, the project introduced two tailored knowledge-based interventions: a Financial Literacy Module and a Community Business Plan Template. The program was implemented through three key stages: program socialization, capacity-building workshops, and follow-up mentoring. Training sessions focused on basic financial management—including budgeting, cash flow recording, and expenditure planning—and on constructing a feasible business plan appropriate to the community’s economic potential. Post-training mentoring demonstrated significant improvements, with participants beginning to apply systematic financial recording practices and producing a draft community business plan that reflects their developing entrepreneurial understanding. The project showcases the effectiveness of context-sensitive, non-digital knowledge tools in supporting marginalized communities toward greater economic autonomy.